Accountability for improving maternal and newborn health. (October 2016) - Scott, Heather; Danel, Isabella
Abstract : In 2010, the United Nations (UN) launched the Global Strategy for Women's and Children's Health to accelerate progress on maternal and child health. A UN Commission on Information and Accountability, established to ensure oversight and accountability on women's and children's health, outlined a framework with three processes: monitor, review, and act. This paper assesses progress on these processes. Effective monitoring depends on a functional civil registration and vital statistics system. Review requires counting all deaths and identifying contributing factors. The final, critical step is action to prevent similar deaths. Maternal death surveillance and response includes these steps and strengthens accountability. Strategies are underway to improve accountability for severe maternal morbidity and perinatal mortality. The post-2015 agenda adds greater focus on reducing inequalities, increasing availability of quality, disaggregated data, and accountability for human rights. This agenda requires engagement with communities and health providers – the foundation of accountability for women's and children's health. Highlights: Global goals and targets for women's and children's health have been defined. An accountability framework was developed, whose processes are monitor, review, and act. Civil registration, vital statistics and MDSR are key components of accountability for maternal and child health. Accountability processes for maternal morbidity and perinatal mortality are underway. There is greater focus on reducing inequities in the post-2015 development agenda.